Clinical insights and management strategies in Takotsubo cardiomyopathy: a comprehensive review - Arewar, Akansha; Dhankikar, Suraj; Besekar, Smruti; Bhosle, Marvel; Besekar, Diptesh (International Journal of Basic & Clinical Pharmacology, 2025)
Takotsubo cardiomyopathy (TCM) is characterized by transient left ventricular dysfunction typically triggered by stressors, presents diagnostic challenges resembling acute coronary syndrome (ACS). This comprehensive review synthesizes diverse triggers (stress, illness, therapies), diagnostic complexities (variability in criteria, imaging modalities), and management strategies (supportive care, tailored medications). Despite favourable outcomes with reversible ventricular dysfunction, heightened risks in specific cohorts (e.g., malignancies, post-PCI) underscore the need for refined diagnostic criteria and optimized therapies. Prospective studies are essential to enhance understanding and management of TCM, aiming to improve clinical outcomes and patient care.